(untitled) (Medical Forum Monthly, 2024)
Objective: The present study was conducted to assess the presentation and etiological aspects of tuberculosis cervical lymphadenopathy for early detection, diagnosis and prompt specific therapy. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Department of Surgery and ENT of Allama Iqbal Memorial Hospital Sialkot from July 2009 to July 2014. Materials and Methods: Data was collected including history, family history, socioeconomic status, history of contact and symptoms. They have already undergone FNAC and only those with inconclusive FNAC underwent excision biopsy. Results: Total sample size was 372 males and females were 232, age range of 0 to 70 years. The younger was a newborn of 2 months of age with history of tuberculosis in mother and the oldest was a 70 year of age with prolonged history of pulmonary tuberculosis. Conclusion: Frequency of tuberculosis is more common in Sialkot district. The main reason of prevalence of tuberculosis is poor hygiene, poverty, overcrowding, tanneries spill over contaminating drinking water. Timely diagnosis is better option in order to reduce such incidence and therapy reducing cost of treatment.